Study of Suicide Cases in Bhopal Region: An Autopsy Study - Patel , D; Jain, A; Khilji, S; Chouksey , V (Journal of Indian Academy of Forensic Medicine, 2024)
The act or incident of voluntarily and intentionally taking one's own life. Suicide is not a new phenomenon in human history; suicide is as  old as mankind itself, and its origins may be traced all the way back to the dawn of civilization. The present study was conducted in the  department of Forensic Medicine and Toxicology Gandhi Medical College, Bhopal, Madhya Pradesh on a total of 686 cases of suicide  brought to the mortuary for post-mortem examination. Highest proportions of cases 243 (35.3%) were in their third decade of life,  implying that suicide is most common in younger age group, followed by people in their fourth decade of life 160 (23.3%). Male victims  predominated (68.6%). Present study predicts unemployment and poverty as being one of the important risk factors for suicide. Most of  the victims belonged to the Hindu religion (93.6%). In my study maximum proportion of cases were married 490 (71.4%), When we look  at the presence of any past illness, 19.4% cases were having some form of chronic physical and mental disorders at the time of committing  suicides. Although seasonal variation is also significant, the present study reveals highest number of cases in summer season (75.7%).  Most common mode of committing suicide was hanging 306 (44.61%), followed by poisoning 283 (41.25%). Least proportion i.e., 1  (0.15%) of deceased chooses firearms as mode of committing suicide.
Keywords: Autopsy; Suicide methods; Poisoning; Hanging